The Relationship between Characteristics, Knowledge and Motivation of Parents on Actions to Prevent Tooth Decay in Elementary School Children - Liencewas, Kezia Puspa; Sihombing, Enna Rossalina (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2024)
Oral health is a recurring problem because children are still in the transition from baby teeth to permanent teeth. At this stage, the child is still dependent on the parents; therefore, the role of the parents is to teach and communicate the importance of dental and oral health. This research aims to identify the characteristics, knowledge, and motivation of parents with the preventive damage to children. This study design used cross-sectional study approach and the number of samples used in this study was 111 parents with a total sampling technique. The statistical analysis of the study uses Kendall's Tau C. Research results obtained by respondents: parents aged 35-45 years as many as 64 (57.7%), females by 85 (76.6%), high school education/PT 84 (75.7%) parents, and income levels 4,000,000 as 80 (7.1%) parents. Statistical tests have shown that there is a relationship between knowledge (p-value = 0.000) and parental motivation (p-value = 0.000) with the prevention of tooth decay in children, but no relationship between age (p-value = 0.424), gender (p-value = 0.01), education level (p-value = 0.101) and parental income level (p-value = 0.454) with a dental safety measure on grades 1-3. Therefore, oral health education is necessary to maintain parental knowledge and motivation.